Numerical study on liquid ammonia direct injection spray characteristics under engine-relevant conditions. (15th March 2023) - Zhang, Yanzhi; Xu, Leilei; Zhu, Yizi; Xu, Shijie; Bai, Xue-Song
Abstract: This paper reports on CFD modeling of the fuel/air mixing characteristics of liquid ammonia under direct injection engine-relevant conditions. Several questions are addressed including, whether the widely used Lagrange particle tracking (LPT) spray models developed for traditional fossil fuels are suitable for ammonia spray, whether certain improvement of the current models should be introduced, and under what conditions the improvement of models needs to be considered. It is found that liquid ammonia spray characteristics can be well reproduced by the current Lagrange-based spray models under non-flash boiling conditions. However, there are obvious gaps between measurements and predictions under strong flash boiling conditions. A strong flash boiling region is found near the nozzle while its intensity decreases downstream due to the significant cooling effect of ammonia spray, and initial superheat degree defined as the ratio of ambient pressure to the saturation vapor pressure at initial fuel temperature, can be adopted to determine the boundary of flash boiling model that needs to be employed in the modeling of liquid ammonia spray. Spray included angle is a crucial parameter within the LPT simulation framework to reproduce the collapse effect for multi-plume sprays. The flash model considering only the evaporation promotion effect cannot replicate the ammonia spray characteristics and it does not result in obvious differences compared with the results from the normal evaporation model. Liquid ammonia is a thermal sensitive fuel and has a strong tendency of flash boiling, and a more accurate flash boiling model that considers the thermal breakup effect should be proposed to accurately predict ammonia fuel/air mixing characteristics under wide engine-relevant conditions. Highlights: DI characteristics of liquid ammonia under various conditions are explored. Different vaporization models for ammonia spray are evaluated in detail. Ammonia spray behaviors can be well predicted under non-flash boiling condition. The thermal breakup effect caused by flash boiling must be considered in modeling.